Titanium Allergy Caused by Dental Implants: A Systematic Literature Review and Case Report - Poli, Pier Paolo; de Miranda, Fábio Vieira; Polo, Tárik Ocon Braga; Santiago Júnior, Joel Ferreira; Lima Neto, Tiburtino José; Rios, Bárbara Ribeiro; Assunção, Wirley Gonçalves; Ervolino, Edilson; Maiorana, Carlo; Faverani, Leonardo Perez (Materials, 2021)
(1) Background: Hypersensitivity reactions to metals may arise in predisposed patients chronically exposed to metallic materials, including dental implants made of titanium alloys. The purpose of this article was to systematically review titanium allergy manifestations in patients treated with dental implants and report a clinical case; (2) Methods: A systematic electronic search was performed for articles published in the English language until July 2021. The following eligibility criteria were adopted: (1) Population: individuals undergoing titanium and/or titanium alloy implant-supported rehabilitations; (2) Exposure: peri-implant soft tissue reactions attributable to implant insertion; (3) Outcome: evidence of titanium allergy, diagnostic methods, and forms of resolution; (3) Results: The included studies, in summary, presented evidence that titanium should not be considered an inert material, being able to trigger allergic reactions, and may be responsible for implant failure. A 55-year-old male patient received 3 implants in the posterior region of the left mandible and presented an epulis-like lesion developed from the peri-implant mucosa. The immunohistochemical analysis of the biopsy specimen confirmed the initial diagnosis of allergic reaction to titanium; (4) Conclusions: Although the evidence is weak, and titanium allergy has a low incidence, hypersensitivity reactions should not be underestimated. A rapid and conclusive diagnosis is mandatory to prevent further complications.